2015
DOI: 10.4103/1319-2442.164565
|View full text |Cite
|
Sign up to set email alerts
|

Association of high-sensitive C-reactive protein and dialysis adequacy with uremic pruritus

Abstract: Uremic pruritus is a difficult symptom in chronic hemodialysis (HD) patients, and its patho-physiological mechanism remains unknown. To determine the relationship between pruritus and C-reactive protein as well as dialysis adequacy among the HD patients, we studied 241 chronic HD patients in Shiraz dialysis centers, Iran. The patients were selected by convenient sampling and the data were collected using a checklist, interview and lab tests. The mean age of our patients was 53.9 ± 16.3 years and 128 (53.1%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
5
13
0
1
Order By: Relevance
“…The result of our study showed, dialysis adequacy was less than international targets (9), which is consistent with the results of different studies (6,8). The results of this study indicated, dialysis inadequacy in routine dialysis using conventional filters, blood flow and dialysate flow rate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The result of our study showed, dialysis adequacy was less than international targets (9), which is consistent with the results of different studies (6,8). The results of this study indicated, dialysis inadequacy in routine dialysis using conventional filters, blood flow and dialysate flow rate.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies suggested that increased rate of blood flow in hemodialysis device increases dialysis adequacy without increasing duration and cost of dialysis (7). Different studies showed that high blood flow is a convenient tool to increase dialysis adequacy (8,9). However, increasing blood flow can also decrease dialysis adequacy due to vascular access type, hypotension and muscular cramps.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [29–33] have revealed that a variety of inflammation factors participate in the pathogenesis of UP. A study [34] has revealed that the complex microenvironment network formed by inflammatory factors and the persistent inflammation state play important roles in the pathogenesis of the repeat attacks of pruritus. A study [35] has suggested that in UP patients, stem cell factors were significantly increased, and the elevation of stem cell factors could recruit chemokines and stimulate mastocyte proliferation and activation.…”
Section: Discussionmentioning
confidence: 99%
“… 7 10 Besides, we and others found that the adequacy of dialysis and the clearance of pruritogenic substances could influence the severity of pruritus. 11 13 …”
Section: Introductionmentioning
confidence: 99%